A comparative analysis of Aconiti Lateralis Radix and processed products using UHPLC-Q-TOF-MS combined with multivariate chemometrics strategies. Issue 1 (20th January 2020) - Sun, Lili; Liu, Fan; You, Guangjiao; Feng, Tao; Wang, Meng; Liu, Yanan; Ren, Xiaoliang; Deng, Yanru
Abstract: An approach exploiting ultrahigh-performance liquid chromatography (UHPLC) fingerprints and multivariate chemometrics to explore the rationality of processing for Aconiti Lateralis Radix is here proposed. UHPLC fingerprints were established to analyze crude Aconiti Lateralis Radix and two processed products (black slices and white slices). The implemented chemometrics methods, including Ward's method and principal component analysis (PCA), could lead to better visualized classification of crude and processed products. Inspection of a Ward's method dendrogram and PCA score plot indicated that all samples belonged to two clusters (crude group and processed group). Subsequently, partial least squares discriminant analysis (PLS-DA) was conducted to obtain the significant chemical markers for discrimination of the crude and processed productions. Additionally, a counter-propagation artificial neural network (CP-ANN) was performed to confirm the chemical markers obtained from PLS-DA. Finally, the chemical markers were identified using ultrahigh-performance liquid chromatography/quadrupole-time-of-flight mass spectrometer (UHPLC-Q-TOF/MS). This strategy has the potential to assess the rationality of processing for Aconiti Lateralis Radix and other Chinese herbal medicines. GRAPHICAL ABSTRACT: